Incidence and determinant factors of delirium in children in the PICU: A systematic review - Hermin Mardiana; Mega Hasanul Huda; Nani Nurhaeni; Nur Agustini (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Delirium in children admitted to the Pediatric Intensive Care Unit (PICU) is an acute neuropsychiatric complication associated with increased morbidity, mortality, length of stay, and long-term neurocognitive impairment. Its incidence ranges from 17–65.6% and exceeds 90% in infants. Various determinant factors including young age, developmental delay, mechanical ventilation, benzodiazepine sedation, metabolic disturbances, physical restraints, and severity of illness have been identified in previous studies. Purpose: To identify the incidence and determinant factors of delirium in children hospitalized in the PICU. Method: A systematic review design with narrative synthesis following PRISMA 2020 guidelines was employed. Literature searches were conducted in PubMed, Scopus, Web of Science, and Google Scholar. Study selection followed PICOS criteria, and methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. Due to heterogeneity in delirium assessment tools, populations, and effect sizes, analysis was conducted using a narrative synthesis approach. Results: Eight studies met the inclusion criteria. The most consistent determinant factors of delirium included developmental delay (OR 3.34–4.20), mechanical ventilation (OR 3.7–6.02), benzodiazepine use (OR 2.89–5.05), high PRISM/PIM scores, hypoxia, metabolic disturbances (OR 3.73), and the use of physical restraints (OR 4.67–5.86). PICU length of stay increased the risk of delirium by 1.1 times for each additional day. Conclusion: Delirium in children in the PICU is a multifactorial condition influenced by biological, clinical, pharmacological, and environmental factors. Prevention efforts should include early detection, routine screening using validated instruments, minimization of high-risk sedation, optimization of ventilation management, environmental modifications to support sleep patterns, and family involvement.